(untitled) (Global Journal of Science Frontier Research, 2012)
Machinery management tries to control maintenance and operation costs by reducing agricultural machinery damages as well. Today, nanotechnology has an important role in reducing engine wear costs by using nano particles in engine oils. To study the effect of nano oil on agricultural engines, performance of eight Massey Ferguson model 399, tractors manufactured in Iran were studied. Each oil sample was analyzed by atomic absorption spectrometry. In addition, Particle Quantifier (PQ), total base number (TBN), viscosity, fuel and water pollution tests were also applied. The results showed that usage of nano diamond oil additive in agricultural tractor engines would reduce wear in cylinders, gaskets, drive shafts, gears, camshaft and valve mechanisms by 68 percent. Also reduced wear was shown in piston ring, bearing, gaskets and exhaust valves by 64 percent. Furthermore, fuel consumption proved a reduction of 21 percent compared to conventional oil use.